1982
DOI: 10.1002/bjs.1800691011
|View full text |Cite
|
Sign up to set email alerts
|

A trial of glucagon in the treatment of painful biliary tract disease

Abstract: Seventy-one patients with a clinical diagnosis of painful biliary tract disease have been entered into a double-blind trial of glucagon. Twenty-eight were excluded as gallstones were not proved: of the remainder, 21 patients received glucagon and 22 placebo. Glucagon-treated patients were pain free 14.26 h (+/- 2.77 s.e.m.) after commencing treatment compared to 29.14 h (+/- 6.01 s.e.m.) for the placebo group (P less than 0.05). Tenderness in the right hypochondrium showed a significant improvement when assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, its spasmolytic action has been accompanied by metabolic consequences, leading to an inappropriate state of hyperglycaemia (Stower et al, 1982). The metabolic activity of glucagon is dependent on the intact molecule, when it binds to liver plasma membranes and activates adenyl cyclase and lipolysis (Frandsen et al, 1981;Jorgensen et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its spasmolytic action has been accompanied by metabolic consequences, leading to an inappropriate state of hyperglycaemia (Stower et al, 1982). The metabolic activity of glucagon is dependent on the intact molecule, when it binds to liver plasma membranes and activates adenyl cyclase and lipolysis (Frandsen et al, 1981;Jorgensen et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…However, the smooth muscle relaxant properties of glucagon have only relatively recently been utilised in clinical medicine. Therapeutic studies have centred mainly on the treatment of biliary tract disease when intravenous glucagon was found to be effective in relieving pain and cystic duct obstruction (Paul, 1979;Stower et al, 1982 Figure 1 Glucagon:glucagon-(1-21)-peptide structure. Boxed area represents the 8 amino acids cleaved from glucagon to obtain glucagon-(1-21)-peptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding 21 patients (no radiological evidence of gallstones) it was concluded that glucagon reduced the amount of pethidine administered for analgesia and the mean time in hours for the patient to become pain free was significantly reduced (14.26 vs 29.14 h). The dose was a 1 mg bolus followed by a 1 mg infusion over 4 h 34 …”
Section: Clinical Usesmentioning
confidence: 99%